Angiotensin-converting enzyme 2 inhibits high-mobility group box 1 and attenuates cardiac dysfunction post-myocardial ischemia - Qi, Yan Fei (J Mol Med (Berl), 2016)
High-mobility group box 1 (HMGB1) triggers and amplifies inflammation cascade following ischemic injury, and its elevated levels are associated with adverse clinical outcomes in patients with myocardial infarction (MI). Angiotensin-converting enzyme 2 (ACE2), a key member of vasoprotective axis of the renin-angiotensin system (RAS), regulates cardiovascular functions and exerts beneficial effects in cardiovascular disease. However, the association between HMGB1 and ACE2 has not been studied. We hypothesized that overexpression of ACE2 provides cardioprotective effects against MI via inhibiting HMGB1 and inflammation. ACE2 knock-in (KI) mice and littermate wild-type (WT) controls were subjected to either sham or coronary artery ligation surgery to induce MI. Heart function was assessed 4 weeks after surgery using echocardiography and Millar catheterization. Tissues were collected for histology and analysis of the expression of HMGB1, RAS components, and inflammatory cytokines. ACE2 in the heart of the ACE2 KI mice was 58-fold higher than WT controls. ACE2-MI mice exhibited a remarkable preservation of cardiac function and reduction of infarct size in comparison to WT-MI mice. Notably, ACE2 overexpression significantly reduced the MI-induced increase in apoptosis, macrophage infiltration, and HMGB1 and pro-inflammatory cytokine expression (TNF-α and IL-6). Moreover, in an in vitro study, ACE2 activation prevented the hypoxia-induced cell death and upregulation of HMGB1 in adult cardiomyocytes. This protective effect is correlated with downregulation of HMGB1 and downstream pro-inflammatory cascades, which could be useful for the development of novel treatment for ischemic heart disease.